Adolescent male fertility following reduced‐intensity conditioning regimen for hematopoietic stem cell transplantation in non‐malignant disorders. (23rd May 2019) - Zhao, Jun; Beebe, Kristen; Magee, Kyrie; Salzberg, Dana; Stahlecker, Jennifer; Miller, Holly K.; Adams, Roberta H.; Lipskind, Shane; Walsh, Alexandra; Mirea, Lucia; Ngwube, Alexander
Abstract: Introduction: The effects of RIC for HSCT on male fertility remain unknown. We investigated spermatogenesis and gonadal hormonal status among adolescent male patients who received RIC HSCT for non‐malignant diseases. Patients and Methods: Patients with non‐malignant disease who had undergone a RIC HSCT were recruited and evaluated for spermatogenesis via semen analysis and gonadal hormonal function via serum hormone levels. Those who had received prior chemotherapy or radiation were excluded from the study. We reviewed the charts to record demographic factors, conditioning regimen and complications during and after transplant. Results: Five patients were enrolled. The median age at the time of transplant was 15 years (range, 11‐19 years), and the median time between bone marrow transplant and semen analysis was 5 years (range, 3‐11 years). Median age of patients was 20 years (range, 18‐25 years) at the time of the study. Serum FSH and LH levels were elevated in four patients, and inhibin B levels were low for age in three patients. Semen analysis showed two patients had azoospermia, and the remaining three patients showed severe oligozoospermia. Normal morphology and motility were seen in only one patient. Conclusion: This case series suggests that RIC transplants may be associated with impaired spermatogenesis and sequential follow‐up is necessary given the potential for either permanent impairment or delayed recovery. Further larger studies are needed to confirm these findings.